Assessment of extremely low frequency magnetic field exposure from GSM mobile phones. Issue 3 (6th November 2013) - Calderón, Carolina; Addison, Darren; Mee, Terry; Findlay, Richard; Maslanyj, Myron; Conil, Emmanuelle; Kromhout, Hans; Lee, Ae‐kyoung; Sim, Malcolm R.; Taki, Masao; Varsier, Nadège; Wiart, Joe; et al.
Abstract Although radio frequency (RF) electromagnetic fields emitted by mobile phones have received much attention, relatively little is known about the extremely low frequency (ELF) magnetic fields emitted by phones. This paper summarises ELF magnetic flux density measurements on global system for mobile communications (GSM) mobile phones, conducted as part of the MOBI‐KIDS epidemiological study. The main challenge is to identify a small number of generic phone models that can be used to classify the ELF exposure for the different phones reported in the study. Two‐dimensional magnetic flux density measurements were performed on 47 GSM mobile phones at a distance of 25 mm. Maximum resultant magnetic flux density values at 217 Hz had a geometric mean of 221 (+198/−104) nT. Taking into account harmonic data, measurements suggest that mobile phones could make a substantial contribution to ELF exposure in the general population. The maximum values and easily available variables were poorly correlated. However, three groups could be defined on the basis of field pattern indicating that manufacturers and shapes of mobile phones may be the important parameters linked to the spatial characteristics of the magnetic field, and the categorization of ELF magnetic field exposure for GSM phones in the MOBI‐KIDS study may be achievable on the basis of a small number of representative phones. Such categorization would result in a twofold exposure gradient between high and low exposure based on type of phone used, although there was overlap in the grouping. Bioelectromagnetics. 35:210–221, 2014. © 2013 Wiley Periodicals, Inc.